On the “Plesionika martia” (A. Milne-Edwards, 1883) species group in Indian waters - Chan, Tin-Yam; Hsu, Chia-Yu; Kumar, Appukuttannair Biju; Chang, Su-Ching (Zootaxa, 2020)
Material of the “Plesionika martia” (A. Milne-Edwards, 1883) species group from India had been reported as either P. martia or P. semilaevis Bate, 1888. Recent collection, however, revealed that both P .martia and P. semilaevis occur in Indian waters. COI barcoding gene sequence comparisons of the Indian and topotypic material of the four known species of the “P. martia” group showed that the Andaman Sea specimen is most similar to the topotypic specimens of P. martia even though there is high genetic divergence between them. For P. semilaevis, large sequence divergence is found in the topotypic material from the Philippines while the Indian specimens are genetically similar to one of the topotypic specimens. The characteristics of the Indian material of both species are described and illustrated.